Dual orexin receptor antagonists show distinct effects on locomotor performance, ethanol interaction and sleep architecture relative to gamma-aminobutyric acid-A receptor modulators - Ramirez, Andres D.; Gotter, Anthony L.; Fox, Steven V.; Tannenbaum, Pamela L.; Yao, Lihang; Tye, Spencer J.; McDonald, Terrence; Brunner, Joseph; Garson, Susan L.; Reiss, Duane R.; Kuduk, Scott D.; Coleman, Paul J.; et al. (Frontiers in Neuroscience, 2013)
Dual orexin receptor antagonists (DORAs) are a potential treatment for insomnia that function by blocking both the orexin 1 and orexin 2 receptors. The objective of the current study was to further confirm the impact of therapeutic mechanisms targeting insomnia on locomotor coordination and ethanol interaction using DORAs and gamma-aminobutyric acid (GABA)-A receptor modulators of distinct chemical structure and pharmacological properties in the context of sleep-promoting potential. The current study compared rat motor co-ordination after administration of DORAs, DORA-12 and almorexant, and GABA-A receptor modulators, zolpidem, eszopiclone, and diazepam, alone or each in combination with ethanol. Motor performance was assessed by measuring time spent walking on a rotarod apparatus. Zolpidem, eszopiclone and diazepam [0.3–30 mg/kg administered orally (PO)] impaired rotarod performance in a dose-dependent manner. Furthermore, all three GABA-A receptor modulators potentiated ethanol- (0.25–1.5 g/kg) induced impairment on the rotarod. By contrast, neither DORA-12 (10–100 mg/kg, PO) nor almorexant (30–300 mg/kg, PO) impaired motor performance alone or in combination with ethanol. In addition, distinct differences in sleep architecture were observed between ethanol, GABA-A receptor modulators (zolpidem, eszopiclone, and diazepam) and DORA-12 in electroencephalogram studies in rats. These findings provide further evidence that orexin receptor antagonists have an improved motor side-effect profile compared with currently available sleep-promoting agents based on preclinical data and strengthen the rationale for further evaluation of these agents in clinical development.